A 90-day intervention study of honey-black cumin and Curcuma xanthorrhiza supplementation on hematological profiles in stunted children - Hardia, Lukman; Akrom, Akrom; Sulistyani, Nanik; Sun, Suny; Hidayati, Titiek (Pharmaciana, 2025)
The preparation of honey-black cumin and Curcuma xanthorrhiza to improve the hematological profile of stunted children is an innovation in utilizing local resources. The primary active components of the supplement, fructose, tymoquinone, and curcumin, have demonstrated a variety of biological activities in the lab. This study aims to determine the effect of consuming honey-black cumin and Curcuma xanthorrhiza on the hematological profile of stunted children. The research method employed a quasi-experimental design with a pre- and post-test, including a control group. The 40 subjects of stunted children were divided into two groups (stunting control and stunting intervention). Univariate analysis examined demographic characteristics, while independent samples t-test and paired samples t-test were used to study numerical data. Results: Statistical analysis of paired sample t-tests revealed that equipping the stunting group with honey-black cumin and Curcuma xanthorrhiza significantly increased lymphocyte count (p <0.001) and decreased neutrophil count (p <0.001). The number of neutrophils and lymphocytes in the intervention stunting group was significantly different (p<0.001) from the control stunting group, according to independent sample t-test findings. Conclusion: A 90-day intervention of honey-black cumin and Curcuma xanthorrhiza improved the levels of leukocyte, lymphocyte, and neutrophil in stunted children.